Lowriders to the center of the Earth - Camper, Cathy; d (San Francisco : Chronicle Books, 2016)
Lupe Impala, Elirio Malaria, and El Chavo Octopus are now the proud owners of their own garage--but when a series of earthquakes hits their town and Genie, their beloved cat, disappears, they find themselves traveling to the realm of Mictlantecuhtli, Aztec god of the Underworld, who is keeping Genie prisoner.
Booklist, June 2016.
Bulletin (Center for Children's books), July 2016.
Kirkus Review, May 2016.
3.0
3-6
Text mainly in English with some Spanish words and phrases.
Keywords: Lowriders -- Comic books, strips, etc. -- Juvenile fiction; Aztec gods -- Comic books, strips, etc. -- Juvenile fiction; Mexican Americans -- Comic books, strips, etc. -- Juvenile fiction; Lowriders -- Fiction; Aztecs -- Fiction; Gods -- Fiction; Mexican Americans -- Fiction; Lowriders -- Comic books, strips, etc. -- Fiction; Aztecs -- Comic books, strips, etc. -- Fiction; Gods and goddesses -- Comic books, strips, etc. -- Fiction; Mexican Americans -- Comic books, strips, etc. -- Fiction; Graphic novels